(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2015)
To determine the prevalence of orbital and ocular manifestations in acute leukemia at the time of presentation, sixty (60) patients diagnosed with acute leukemia were examined for ocular lesions by within two weeks of diagnosis before starting chemotherapy. The detailed ocular examination of both eyes was carried out by the ophthalmologist irrespective of the presence or absence of eye symptoms in all cases. Only 3 out of 60 patients presented with eye symptoms (5%). However, ocular changes were found in 16 patients (26%), 11 with lymphoblastic and 5 with myeloid leukemia. The ocular lesions observed were Intraretinal hemorrhages, decreased Visual acuity, Proptosis, Macular hemorrhage, Cotton wool spots, Papilloedema, Vitrious hemorrhage and Sixth nerve palsy. In view of the high prevalence of asymptomatic ocular lesions in acute leukemia, routine Ophthalmic Examination should be included as a part of evaluation at the time of diagnosis. JCMCTA 2015 ; 26 (1) : 21-24